Behavior of hevea sp amazonic clones under the ecological conditions of Belém, PA, Brazil - Viégas, Rosemary Moraes Ferreira; Viégas, Ismael de Jesus Matos; Pinheiro, Eurico (Pesquisa Agropecuaria Brasileira, 2014)
The performance of 14 amazonian clones of Hevea sp. (IAN 8000, IAN 500, IAN 710, IAN 713, IAN 717, IAN 833, IAN 873, IAN 936, Fx 1042, Fx 2261, Fx 3810, Fx 3925, Fx 4098 and Fx 25) has been studied under the ecological conditions of Belém, PA, Brazil. Eleven years after the installation of the experiment, the clones Fx 25, IAN 717, Fx 3925, Fx 4098, Fx 3810 and Fx 2261 have showed the highest production of dry rubber per tapping, respectively, in grams: 36,6; 33,2; 29,8; 22,9; 19,5; 19,2. Among the most resistant clones to South American Leaf Blight are IAN 717, Fx 3810, Fx 3925 and Fx 4098.